Activity of axitinib in progressive advanced solitary fibrous tumour: Results from an exploratory, investigator-driven phase 2 clinical study. (January 2019) - Stacchiotti, S.; Simeone, N.; Lo Vullo, S.; Morosi, C.; Greco, F.G.; Gronchi, A.; Barisella, M.; Collini, P.; Zaffaroni, N.; Dagrada, G.P.; Frezza, A.M.; Mariani, L.; et al.
Abstract: Background: To explore the activity of axitinib in advanced solitary fibrous tumour (SFT). Patients and methods: In this investigator-driven phase II study on axitinib in advanced and progressive SFT, patients received axitinib, 5 mg bis in day (BID), until progression or limiting toxicity. Pathologic diagnosis was centrally reviewed, distinguishing malignant SFT (M-SFT) and high-grade/dedifferentiated SFT (HG/D-SFT) subtypes. The primary end-point was the overall response rate (ORR) by Choi criteria (Choi). Secondary end-points were response by Response Evaluation Criteria in Solid Tumours (RECIST), progression-free survival (PFS) and overall survival (OS). Results: From April 2015 and October 2017, 17 eligible patients entered the study (metastatic: 17; SFT subtype: 13 M-SFT, 4 HG/D-SFT; prior treatment: 9 antiangiogenics, 5 cytotoxics). All patients were evaluable for response. The best Choi response was seven partial response (PR) (ORR, 41.2%), six stable disease (SD) and four progressions. Choi-ORR was 54% (7/13) when only M-SFTs were considered. Four of seven responsive patients were pretreated with pazopanib. No responses were detected in HG/D-SFT. Best RECIST response was one PR (5.9%), 14 SD and two progressions. Toxicity was as expected. Median Choi-PFS was 5.1 (interquartile range [IQR]: 2.5–14.8) months. Median Choi-PFS was 14.8 (IQR: 5.1–18.0) and 2.8 (IQR: 2.0–5.9) months for patients responsive and non-responsive by Choi, respectively (p = 0.0416). At a 14.4-month median follow-up, median OS was 25.3 months. Conclusion: This study showed that axitinib is active in progressive advanced SFT. One-half of patients carrying the malignant variant of the disease responded, with a >12-month median progression arrest. Responses were better detected with Choi and seen even in patients resistant to other antiangiogenics. Tolerability was good. Highlights: Axitinib was active in progressive advanced malignant solitary fibrous tumour (M-SFT). Responses were usually non-dimensional and detectable by Choi (Choi- overall response rate [ORR] 41%; Response Evaluation Criteria in Solid Tumours. One-half of patients carrying the non–high-grade SFT responded, with a >12-month median progression arrest. Responses were observed also in patients resistant to other antiangiogenics. Tolerability was good.